Agricultural diversification: a strategic factor for growth - Mahmud, Wahiduddin; Rahman, Sultan Hafeez; Zohir, Sajjad (International Food Policy Research Institute, 2000)
Seed-fertilizer technology has had a dramatic influence on cereal production in many developing economies, including Bangladesh. Agricultural diversification is the next stage in transforming traditional agriculture to a dynamic, commercial sector. Diversification in the product mix of agriculture, through a shift toward high-value products, has great potential for accelerating growth rates in production. To exploit this potential, forces within both the supply and the demand sides of the shift are important; but demand forces (the scope of market opportunities for high-value products) play a more important role in the initial stage of the process. Robust diversification cannot take place without exploitation of foreign demand. In low-income economies, domestic demand for high-value products such as fish, livestock products, horticultural products, and vegetables is generally low and does not have a significant impact on agricultural growth rate through diversification. Thus, an export-based strategy is generally the most productive route to follow. In Bangladesh rice contributes about 50 percent of the gross domestic product (GDP) in agriculture and 70 percent of the value of crop production. On the other hand, income elasticity of the demand for rice is low and declining over time (see Chapter 5). Therefore, agricultural diversification is a serious issue in the context of agricultural growth.